Estudo numérico do comportamento de vigas mistas contínuas submetidas a momentos fletores não uniformes em situação de incêndio - Bruno Marani Siciliano (2023)
The behavior of continuous composite beams under fire situation is yet not completely known due to the complexity of the phenomena that occur in this type of structural element. Differently from simply supported beams, in a continuous composite beam, the lower compressed region of the steel profile does not count on the buckling restriction. Therefore, the bottom flange displaces sideward with a twist, as long as the web does not have the necessary stiffness to prevent this occurrence. This phenomenon is called Lateral Distorcional Buckling (LDB), and it is potentiated due to the degradation of mechanical properties of the materials at elevated temperatures. The present work aims at performing a parametric study on continuous composite beams with two spans, submitted to non-uniform bending moments and under fire situation, based on a finite element numerical model developed in ANSYS Mechanical APDL software, validated by a series of real scale experiments. In the study, influences of geometric variables of the composite beams, such as the length of their spans and the dimensions of their cross-section will be evaluated. Moreover, the interference of the variation of the loading level, the temperature-rise curves and the compartmentation of the beams will be studied. An increase in hogging moments at the central support region was observed due to the restriction of the thermal deformations, resulting in the plastification of a great part of the cross section at temperatures lower than 200 °C. Then, with the loss of stiffness of the cross section, buckling become propitious to occur and the capacity of the beam to prevent them determines the temperature in which the hogging moments decrease, i.e., when the efforts redistribution to the mid span occurs. In general, the collapse of the evaluated beams occurred between 600 °C and 700 °C. Properties such as the thickness of the web and lower flange of the steel profile showed to be relevant to the increase of hogging moment peak and to the delay of its decay. The increases of the profile height and the amount of rebar resulted in the elevations of hogging moment peak but highlight the instability.